Cloud-Native Architecture and Conversational AI: Revolutionizing Enterprise Automation - Karthik Reddy Thondalapally, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud-native architectures and AI-powered chatbots represent complementary forces driving a profound transformation in enterprise automation strategies. This comprehensive article explores how organizations across industries are leveraging containerization, microservices, and serverless computing alongside conversational AI capabilities to revolutionize both backend operations and customer-facing interactions. By examining the technological foundations, implementation approaches, and real-world applications across retail, finance, healthcare, and human resources sectors, it uncovers how these integrated technologies deliver unprecedented scalability, resilience, and user engagement. The convergence of infrastructure modernization with intelligent conversational interfaces creates a powerful framework for enterprises seeking to achieve operational excellence while providing intuitive, responsive experiences for both customers and employees.
Keywords: Cloud-Native Transformation; Conversational Automation; Microservices Architecture; Enterprise AI Integration; Digital Workflow Optimization